Phylogenetic relationship and characterization of the complete chloroplast genome of the Coriaria nepalensis Wall. in China, a least concern folk medicine. Issue 2 (2nd April 2020) - Fang, Hailan; Shang, Feineng; Qian, Jun; Duan, Baozhong
Abstract: Coriaria nepalensis Wall. is a toxic Chinese herbal medicine. In this study, the complete chloroplast (cp) genome of C. nepalensis was first reported. The length of the large single-copy (LSC) region was 158, 499 bp, the small single-copy (SSC) region was 18, 411 bp, and the inverted repeats (IRs) region were 26, 552 bp, with 37.76% overall GC content. There were 132 genes in total, including 86 mRNA, 38 tRNA, and 8 rRNA. Phylogenetic analysis showed that C. nepalensis was closely related to Corynocarpus laevigatus .